PENGARUH VARIASI KONFIGURASI POSISI DIAGONAL BRACED CBF TERHADAP PERILAKU STRUKTUR RANGKA BAJA 6 LANTAI DI KOTA PONTIANAK - Bachsin, Nargis Aufa; Violeta, Iona; Yufiansyah (Fakultas Teknik Universitas Panca Bhakti, 2025)
Indonesia is an earthquake-prone region, thus building structures must be designed to withstand seismic forces. One way to strengthen a structure is by using a Concentrically Braced Frame (CBF) system with various bracing position configurations. This study aims to analyze the influence of diagonal bracing position variations on the natural period, maximum displacement, and inter-story drift of a six-story steel structure using ETABS version 22 software. The results show that the structure without bracing produces the highest values for period, displacement, and drift. The direction of bracing installation does not significantly affect the results, as seen in variations 1A–1B, 2A–2B, and 3A–3B, which yield nearly identical outcomes. Discontinuous bracing configurations, such as in 2C–2D and 3C–3D, result in higher drift values. Variations 4A–4B provide better results than 4C–4D due to more uniform bracing distribution. Variation 2A produces the best results, with a period of 2.362 seconds (mode 1) and 1.339 seconds (mode 2), a maximum displacement of 111.81 mm, and drift values of 102.409 mm (X) and 34.139 mm (Y). However, variation 4A is more efficient, with nearly equivalent performance: a period of 2.362 seconds (mode 1) and 1.473 seconds (mode 2), a maximum displacement of 135.41 mm, and drift values of 102.39 mm (X) and 34.14 mm (Y). Keywords: Bracing, Earthquake, Period, Displacement, Drift